Component-interaction automata as a verification-oriented component-based system specification. - Brim, Lubo? (Software engineering notes.)
In the paper, we present a new approach to component interaction specification and verification process which combines the advantages of both architecture description languages (ADLs) at the beginning of the process, and a general formal verification-oriented model connected to verification tools at the end. After examining current general formal models with respect to their suitability for description of component-based systems, we propose a new verification-oriented model, Component-Interaction automata, and discuss its features. The model is designed to preserve all the interaction properties to provide a rich base for further verification, and allows the system behaviour to be configurable according to the architecture description (bindings among components) and other specifics (type of communication used in the synchronization of components).